Protection induced by a glycoprotein E-deleted bovine herpesvirus type 1 marker strain used either as an inactivated or live attenuated vaccine in cattle - Romera, Sonia Alejandra; Puntel, Mariana; Quattrocchi, Valeria; Del Medico Zajac, Maria Paula; Zamorano, Patricia Ines; Blanco Viera, Francisco Javier; Carrillo, Consuelo; Chowdhury, Shafiqul; Borca, Manuel Victor; Sadir, Ana Maria (BMC, 2019)
Background: Bovine herpesvirus type 1 (BoHV-1) is the causative agent of respiratory and genital tract infections; causing a high economic loss in all continents. Use of marker vaccines in IBR eradication programs is widely accepted since it allows for protection of the animals against the disease while adding the possibility of differentiating vaccinated from infected animals. The aim of the present study was the development and evaluation of safety and efficacy of a glycoprotein E-deleted (gE-) BoHV-1 marker vaccine strain (BoHV-1ΔgEβgal) generated by homologous recombination, replacing the viral gE gene with the β-galactosidase (βgal) gene. Results: In vitro growth kinetics of the BoHV-1ΔgEβgal virus was similar to BoHV-1 LA. The immune response triggered by the new recombinant strain in cattle was characterized both as live attenuated vaccine (LAV) and as an inactivated vaccine. BoHV-1ΔgEβgal was highly immunogenic in both formulations, inducing specific humoral and cellular immune responses. Antibody titers found in animals vaccinated with the inactivated vaccine based on BoHV-1ΔgEβgal was similar to the titers found for the control vaccine (BoHV-1 LA). In the same way, titers of inactivated vaccine groups were significantly higher than any of the LAV immunized groups, independently of the inoculation route (p < 0.001). Levels of IFN-γ were significantly higher (p < 0.001) in those animals that received the LAV compared to those that received the inactivated vaccine. BoHV-1ΔgEβgal exhibited an evident attenuation when administered as a LAV; no virus was detected in nasal secretions of vaccinated or sentinel animals during the post-vaccination period. BoHV-1ΔgEβgal, when used in either formulation, elicited an efficient immune response that protected animals against challenge with virulent wild-type BoHV-1. Also, the deletion of the gE gene served as an immunological marker to differentiate vaccinated animals from infected animals. All animals vaccinated with the BoHV-1ΔgE βgal strain were protected against disease after challenge and shed significantly less virus than control calves, regardless of the route and formulation they were inoculated. Conclusions: Based on its attenuation, immunogenicity and protective effect after challenge, BoHV-1ΔgEβgal virus is an efficient and safe vaccine candidate when used either as inactivated or as live attenuated forms.